The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1152/jn.2000.84.3.1667
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Dorsal Premotor Cortex and Pre-Supplementary Motor Area of Humans During an Auditory Conditional Motor Task

Abstract: Using functional magnetic resonance imaging (fMRI), we measured regional blood flow to examine which motor areas of the human cerebral cortex are preferentially involved in an auditory conditional motor behavior. As a conditional motor task, randomly selected 330 or 660 Hz tones were presented to the subjects every 1. 0 s. The low and high tones indicated that the subjects should initiate three successive opposition movements by tapping together the right thumb and index finger or the right thumb and little fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 28 publications
6
43
0
1
Order By: Relevance
“…At the same time, other functional neuroimaging studies reported this same intersection of the SPS with the SFS to be the focus of premotor hand/ arm conditional activity (Deiber et al, 1997;Grafton et al, 1998;Toni et al, 1999;Kurata et al, 2000). These functional neuroimaging findings raised a major problem regarding our understanding of the organization of the dorsal premotor region of the human brain by failing to discriminate between the location of visuomotor hand conditional activity and the FEF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the same time, other functional neuroimaging studies reported this same intersection of the SPS with the SFS to be the focus of premotor hand/ arm conditional activity (Deiber et al, 1997;Grafton et al, 1998;Toni et al, 1999;Kurata et al, 2000). These functional neuroimaging findings raised a major problem regarding our understanding of the organization of the dorsal premotor region of the human brain by failing to discriminate between the location of visuomotor hand conditional activity and the FEF.…”
Section: Discussionmentioning
confidence: 94%
“…Lesions involving this region impair severely the learning and performance of visuomotor hand/arm conditional responses in both human subjects (Petrides, 1985(Petrides, , 1997Halsband and Freund, 1990) and the monkey (Halsband and Passingham, 1982;Petrides, 1982Petrides, , 1986. In addition, functional neuroimaging in normal human subjects has shown reliable activation related to the performance of visuomotor hand/arm conditional responses within the dorsal premotor cortex at the junction of the superior precentral sulcus (SPS) with the superior frontal sulcus (SFS) (Deiber et al, 1997;Grafton et al, 1998;Toni et al, 1999;Kurata et al, 2000). However, on the basis of functional neuroimaging studies, this same general region has also been reported to be the locus of the human homolog of the frontal eye field (FEF) (Paus, 1996;Petit et al, 1997;Corbetta et al, 1998;Luna et al, 1998;Petit and Haxby, 1999;Gagnon et al, 2002;Astafiev et al, 2003;Koyama et al, 2004;Grosbras et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Its activity precedes that of the primary motor cortex in intentional movement (Weilke, 2001). In most of these studies that demonstrate the involvement of the SSMA in volition, auditory cues are chosen for external triggering of movements (e.g., Cunnington, 2002;Toma, 2003;Kurata, 2000).…”
Section: Clues To An Understanding Of Sensory Gatingmentioning
confidence: 99%
“…2). Considerable controversy exists in the brain-imaging literature concerning results for conditional motor tasks, typically in the form of a specific motor act of the hand cued by either an auditory or visual stimulus (Deiber et al, 1997;Grafton et al, 1998;Kurata et al, 2000). Nearly all such studies elicit activity contralateral to the hand used and often more posteriorly in area 6.…”
Section: Posterior Dorsolateral Frontal Activationsmentioning
confidence: 99%